Organización industrial, distribución del ingreso y dinamismo industrial - Cortez, Willy W. (El Colegio de México, A.C., 2003)
This essay presents a theoretical model that explains industrial stagnation in less developed economies through the identification of factors that affect both productivity and demand growth. It is argued that productivity growth depends on variables operating at the firm and industry levels for given values of output and capital. Demand growth, in turn, depends on income distribution, determined by the bargaining position of workers and capitalists. Greater employment rate induces a larger bargaining position of workers to set wage increases, while higher demand in the goods market would allow capitalists to transfer the increases in wage rate onto prices, thus increasing the profit margins per unit of output.